ANALISIS FRAMING PESAN KESALEHAN SOSIAL PADA BUKU UNGKAPAN HIKMAH KARYA KOMARUDDIN HIDAYAT - Fatmawati Fatmawati (al-Balagh : Jurnal Dakwah dan Komunikasi, 2018)
From this book Hikmah Wisdom writer wanted to know how the message of social piety framed and constructed by Komaruddin Hidayat. The method used is constructionist paradigm with qualitative descriptive approach with framing analysis model of Zhongdang Pan and Gerald M. Kosicki. Based on the analysis of the model of Zhongdang Pan and Gerald M. From this research it can be concluded that the book Ungkapan Hikmah with four titles related to the message of social piety emphasizes the attitude of tolerance and peace, this is evidenced by Komaruddin Hidayat's ideas that often emphasize the importance of mutual respect in the midst of differences to create peaceful conditions as an implication of one's faith in Allah SWT.